2022
DOI: 10.1088/2053-1591/ac9c86
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on mechanical and wear behaviour of graphene and zirconia reinforced AA6061 hybrid nanocomposites using ANN and Sugeno-type fuzzy inference systems

Abstract: This research work investigates the mechanical and wear behaviour of graphene (C) and zirconium dioxide (ZrO2) reinforced Aluminium alloy 6061 hybrid nanocomposites (AMMHNCs) fabricated by the ultrasonic-assisted stir casting method. Graphene and ZrO2 are selected as reinforcements for increasing the wear resistance and hardness of the base alloy AA6061. The mixing proportions of graphene and ZrO2 reinforced with AA6061 in weight are 100% AA6061 / 0% Graphene / 0% ZrO2, 98.5% AA6061 / 0.5% Graphene / 1% ZrO2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was observed that an increase in reinforcements resulted in improved mechanical properties, whereas percentage elongation decreased. Furthermore, wear resistance was found to improve with additional reinforcements (Masooth 2022).…”
mentioning
confidence: 95%
“…It was observed that an increase in reinforcements resulted in improved mechanical properties, whereas percentage elongation decreased. Furthermore, wear resistance was found to improve with additional reinforcements (Masooth 2022).…”
mentioning
confidence: 95%